LEGAL PROTECTION OF ABORTION ABUSERS IN THE PREGNANCY OF RAPE IN INDONESIA - Firdaus Pria Pradana; Rahtami Susanti; Bayu Setiawan (UMPurwokerto Law Review, 2020)
Abortion is prohibited except on the basis of indications of medical emergencies and pregnancy due to rape as regulated in Article 75 paragraph (2) of Law Number 36 the Year 2009 Concerning Health. Nevertheless, there are some cases where rape victims who abort their womb are found guilty of violating Article 346 of the Criminal Code. This study discusses the legal protection of abortionists in pregnancy due to rape. The purpose of this study was to analyze the legal protection of victims of rape who had an abortion (abortion provokes). The research method used is a normative juridical approach that is through literature studies that examine secondary data in the form of legislation and other legal documents, research results, results of studies, and other references. The results of this study are that rape victim who did an abortion were not convicted in accordance with Article 75 paragraph (2) of Law Number 36 of 2009 concerning Health and the existence of pre and post-abortion counseling in accordance with Article 37 of Government Regulation Number 61 of 2014 concerning Reproductive Health.Keywords: Legal protection, Abortion, the rape victim